Biomechanical analysis for the IAAF World Championships London 2017 100 m Women's - Bissas, A.; Walker, J.; Tucker, C.; Paradisis, G.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s 100 m final and semi-finals took place on Sunday 6th August in good weather conditions. Jamaica`s Elaine Thompson was one of the main favourites coming into the championships, having won Olympic gold in Rio 2016 and currently holding a world-leading time of 10.71 s. Dafne Schippers and Marie-Josée Ta Lou would also be likely medal contenders, having come close to Elaine Thompson in some Diamond League events leading up to the world championships. Tori Bowie from the USA was also a potential contender, despite losing out to Elaine Thompson in the 2016 Olympic final. In the end, it was Tori Bowie who narrowly beat Marie-Josée Ta Lou on the line to claim the gold medal with a season`s best time of 10.85 s. Ta Lou`s silver medal time of 10.86 s was a personal best. The bronze medal went to Dafne Schippers from lane 9, whilst Elaine Thompson was slow out of the blocks and was unable to come back, finishing in 5th place with a time of 10.98 s.